Evaluation of the Effect of Supragingival Scaling on Periodontal Parameters in Pregnant Women with Metabolic Syndrome - Ghousia Sayeed; Sheeja S. Varghese (Journal of Pharmacy and Bioallied Sciences)
Background: Although there are quite a number of studies on the impacts of periodontal therapeutic management on pregnant females, literature on the impact of supragingival scaling on pregnant females with metabolic syndrome (MS) is wanting. The present investigation was meticulously formulated to ascertain the clinical ramifications of supragingival scaling in pregnant individuals diagnosed with MS. Material and Methods: An intervention study was conducted on 47 pregnant females. The gingival index (GI), plaque index, bleeding on probing, probing depth, and clinical attachment level were among the periodontal parameters evaluated. By the end of 20–21 weeks of pregnancy, all participants had received scaling and polishing at the baseline appointment, along with advice on dental hygiene. Periodontal parameters were gathered again during a follow-up appointment 8 weeks post treatment. A 5% threshold for statistical significance was set, and paired t-test and chi-square test were applied for comparison. Results: Lower levels of PI, GI, and BOP 8 weeks post supragingival scaling were noted than at the baseline. The results obtained were statistically significant (P < 0.001) All patients with severe periodontitis (n = 14) before supragingival scaling shifted to milder forms of the disease. Similarly, moderate periodontitis was seen in 20 patients before the start of the study, and after the intervention, it was reduced to 16 patients. Conclusion: In summary, supragingival scaling lowers the incidence of periodontal disease in pregnant MS females. High-risk pregnant women who receive scaling treatment and instruction on oral hygiene on a regular basis have better oral health, which in turn improves the health of their unborn child.